2022
DOI: 10.1007/s13246-022-01124-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of interstitial microwave hyperthermia for hepatic tumors using floating sleeve antenna

Abstract: Microwave hyperthermia is a treatment modality that uses microwaves to destroy cancer cells by increasing their temperature to 41-45°C. This study aims to design, modeling, and simulation of a microwave sleeve antenna for hepatic (liver) hyperthermia. Method: The designed antenna resonated at 2.45 GHz. The antenna was tested in six different 3D liver models: Model A: without a tumor and blood vessels; Model B: with a realistic tumor (2×3 cm) and without blood vessels; Model C: created by adding blood vessels t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Interstitial HT is based on heat generated via a metal antenna made of ferromagnetic material to increase the temperature of tumor tissues [ 11 , 12 ]. However, this method is highly invasive, painful, and can lead to necrosis as far as 1–2 cm from the applied heat source [ 13 ]. Since heat generated by conventional HT methods is distributed in a chaotic manner, improved methods are needed to minimize thermal damage to surrounding healthy tissues.…”
Section: Types Of Conventional Ht Methodsmentioning
confidence: 99%
“…Interstitial HT is based on heat generated via a metal antenna made of ferromagnetic material to increase the temperature of tumor tissues [ 11 , 12 ]. However, this method is highly invasive, painful, and can lead to necrosis as far as 1–2 cm from the applied heat source [ 13 ]. Since heat generated by conventional HT methods is distributed in a chaotic manner, improved methods are needed to minimize thermal damage to surrounding healthy tissues.…”
Section: Types Of Conventional Ht Methodsmentioning
confidence: 99%
“…In this section, we present the methodological framework adopted for our study, which aims to evaluate the applicability of interstitial microwave hyperthermia in the treatment of breast tumors. Our research builds upon a previously established foundation involving the design of a oating sleeve antenna for hepatic tumors, as comprehensively documented in our prior publication [13]. In this study, two distinct 3D breast models were used.…”
Section: Methodsmentioning
confidence: 99%
“…The material properties of the gland of the simple model are illustrated in the table, while the properties for the 100 broconnective/glandular tissues of the realistic model can be found in [19]. It has been reported that breast tumors tend to have gradually lower perfusion and higher basal metabolic rates than the surrounding normal tissues [13,19,20]. Therefore, in both models, we consider the blood ow coe cient and the basal metabolic rate of the tumor to be 5 times less and 20 times more than that of the gland tissues, respectively.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation